The Ancient Sources of Anthropocentrism - Ganowicz-Bączyk, Anita (Studia Ecologiae et Bioethicae, 2009)
Anthropocentrism seems to be a key notion related to the man-nature relation. Probably he is also the most controversial one in environmental ethics. The anthropocentric attitude is sometimes meant to be the main cause of the ecological crisis. One can distinguish at least several stages of the process, which led to this crisis, namely: stage of Magic and Myth, Ancient Times, Middle Ages, and Modern Times. The aim of this article is to show the process of development of an anthropocentric thought in Ancient European culture. Supposedly the critical phase for this process is the so-called Neolithic Revolution. Changes brought by this deeply influenced life of man. Not only affected the transformation of his world-view but also had an impact on the modification of society itself. Mentioned changes led among other things to the rejection of magic and mythical world-view, in which the Universe was perceived as a harmonious and friendly place to live in. A doubt appeared instead, what the place of man in the world really is. These questions reflected in philosophical views of that time. To sum up, the originated by Ancient Greek philosophers outlook on nature, in which nature was recognized as a living organism and a man as an immanent part of it, had been gradually dropped out. It appeared that man falls outside the mechanical laws of nature because he is able to understand them and use this knowledge for his own goals (Democritus), man’s soul makes him transcend nature and dominate it (Socrates), man’s existence is purposeful, he is superior to other material beings as a crown of nature and the most complex and perfect being (Aristotle). This process led to a recognition of the objective existence of the world, which in fact is independent of human cognition. Ultimately, this resulted in the objectification of nature as an object of man’s cognition and research. Nature was then gradually put in opposition to man – the subject of cognition.